Cap Polyposis: A Case Report - Tunam Khadka; Ganesh Kumar Giri; Pasang Sherpa; Nischal Shrestha; Sanjaya Poudyal (Journal of Nepal Medical Association, 2023)
Cap polyposis is a gastrointestinal disease with multiple inflammatory polyps between the distal colon and rectum. Its symptoms overlap with inflammatory bowel disease with typical endoscopic features of multiple sessile polyps in the rectum and sigmoid colon, located at the apices of transverse folds. Microscopically, the polyps consist of elongated, tortuous, and distended crypts covered by a “cap” of inflammatory granulation tissue. In this report, we present a case of a 18-year-old male patient who underwent polypectomy for polyposis in multiple settings. He presented with one year of painless rectal bleeding and polyposis in a recto-sigmoid area on colonoscopy, with a single polyp in the sigmoid area and multiple polyps in the rectum. He was managed with immediate and interval polypectomy. Though cap polyposis is rare, it can be cured as it is laparoscopically resectable.